Asymptotic Insights for Projection, Gordon–Lewis, and Sidon Constants in Boolean Cube Function Spaces - Defant, A. (2024)
The main aim of this work is to study important local Banach space constants for Boolean cube function spaces. Specifically, we focus on mathcalB_{mathcalS}^{N}, the finite-dimensional Banach space of all real-valued functions defined on the N-dimensional Boolean cube {-1, +1}^{N} that have Fourier–Walsh expansions supported on a fixed family of subsets of {1, ldots , N}⁠. Our investigation centers on the projection, Sidon, and Gordon–Lewis constants of this function space. We combine tools from different areas to derive exact formulas and asymptotic estimates of these parameters for special types of families depending on the dimension of the Boolean cube and other complexity characteristics of the support set ⁠. Using local Banach space theory, we establish the intimate relationship among these three important constants.